The Effect of Stimulating Games with Stickers with Vowal Letters Into Meaningful Words on Reading Interest in Children Aged 5-6 Years at Bintang Kecil Kindergarten, Rawamangun Village, East Jakarta - Ismiati, Ismiati; Puridawaty, Brigita (Kirana Publisher (KNPub), 2025)
This study aims to find out and analyze the effect of the stimulation of the voca letter sticker game into a meaningful word on the interest in reading in children aged 5-6 years at Kindergarten Bintang Kecil Rawamangun, East Jakarta. This study uses a quasi-experimental design with a pretest-posttest approach. The subjects of the study were children aged 5-6 years who participated in learning with the media of vowel stickers. The vaid and reliability of the research instrument were tested, with the results showing that all items of the vaid questionnaire were vaid (correlation coefficient > rtable = 0.5494) and high reliability (Cronbach's Apha = 0.918). These findings affirm the importance of creative and interactive learning methods in early childhood education and make a significant contribution to the development of more innovative curricula and learning strategies. This research can make a positive contribution to the development of more effective curriculum and learning strategies for early childhood education. In addition, it is hoped that this study can also provide a more comprehensive understanding of the importance of applying the method of stimulating the game of Vocal letter stickers into meaningful words to the interest in reading in children aged 5-6 years.